A Survey on Enterprise Resource Planning and Building Information Modeling Integration: A Construction 4.0 Perspective - Galagali, Anagha Anirudh; Sandbhor, Sayali; Ruikar, Kirti (Buildings (Basel), 2024)
Managing the fragmented nature of information generated on construction sites and firms is the need of the hour. Building Information Modeling (BIM) and Enterprise Resource Planning (ERP) are the most prevalent information systems (ISs) used in the construction industry, with varied capabilities but also with significant overlap. It is essential to analyze the current state of Common Data Environments (CDEs) that support both BIM and ERP as separate systems, as well as those that facilitate their integration. This analysis will ultimately help establish a practical framework for implementing this integration, enabling smoother information flow and enhanced utilization in construction projects. This paper presents a bibliometric analysis and provides a global perspective on research developments in the field of construction ERP and its integrations with BIM. It consolidates publication data from various databases (e.g., Scopus and Web of Science) as per geographical spread, authors, and number of publications as per the keyword search. It observes key research themes in each phase of the analysis. This paper concludes that although the existing literature has established the benefits of BIM and ERP integration, research is still in its nascent stage and identifies research gaps that can be taken up for further research.